2023
DOI: 10.1002/acn3.51932
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between spinal cord stimulation analgesia and cortical dynamics in pain management

Li Chen,
Zhen Zhang,
Rui Han
et al.

Abstract: AimSpinal cord stimulation (SCS) is an effective method to treat neuropathic pain. It is necessary to identify the responders of SCS analgesia before implantation. The aim of this study is to investigate the relationship between the cortical dynamics and SCS analgesia responders in pain management.MethodsResting‐state EEG recording was performed in patients who underwent short‐term implantation of spinal cord stimulation for pain therapy. We then did spectral analysis to capture the pattern of cortical oscilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…During postoperative follow-up, a reduction in VAS score of 50% or more compared to the baseline score upon admission was de ned as a responder [13] .…”
Section: Clinical Outcomes and Follow-upmentioning
confidence: 99%
See 1 more Smart Citation
“…During postoperative follow-up, a reduction in VAS score of 50% or more compared to the baseline score upon admission was de ned as a responder [13] .…”
Section: Clinical Outcomes and Follow-upmentioning
confidence: 99%
“…However, for patients with severe pain, SCS may not be fully effective, and some patients continue to experience moderate or severe pain after discharge. A recent study showed that 41.7% of ZAP patients treated with SCS had less than 50% pain reduction at discharge [13] . Another review summarized the long-term follow-up of various types of SCS in the treatment of PHN, noting that 32.1% of patients still had unsatisfactory pain relief [14] .…”
Section: Introductionmentioning
confidence: 99%